Mid-Term Outcome of the Hybrid Method of Ventricular Septal Defect Closure in Children. - Akkerbez Adilbekova; Bakhytzhan Nurkeev; Shukhrat Marassulov; Saken Kozhakhmetov (National Scientific Medical Center, 2024)
Objective: To describe the clinical experiences and mid-term follow-up results of the hybrid method of ventricular septal defect closure in children. Methods: This study was a combined - multidirectional cohort. Between May 2016 and December 2020, 250 patients with isolated VSD (or residual VSD after a previous repair) underwent surgery by the hybrid method at the pediatric cardiac surgery department in the National Scientific Medical Center. This study adopted a combined and multidirectional cohort approach, initially starting as a retrospective cohort and later transitioning into a prospective cohort. Results: A total of 250 patients in this cohort underwent hybrid VSD closure, of which 233 (93.2%) patients were successful, 16 (6.4%) patients were converted to the traditional method and 1 (0.4%) death occurred. New trivial or mild tricuspid regurgitation was detected in 35 patients (15%) and aortic regurgitation in 9 patients (3.9%) by intraoperative TEE. For the remaining 10 patients with incomplete right bundle branch blocks the sinus rhythm was restored in follow-up. In addition, the left ventricular ejection fraction improved over time. One of the important points after surgery is the deformation of the chest. In 122 (91%) patients, there is no deformation; unfortunately, in 12 (9%) patients, there is deformation. Conclusions: The hybrid method is a rapidly developing technique that has been safe and effective in a selected group of patients in recent years. The advantages of this method are minimum incision namely the size and length of the postoperative scar from 2 to 4 cm. Also, no myocardial injury, and reduces operation time, intensive care unit stay, and hospital stays.